On the way to protectorate - Esipov, Vladislav V.; Edinarhova, Nina E. (The New Research of Tuva, 2013)
A review of the publication: Vasilenko V. A. On the way to protectorate (from the second half of 19th to 1914). LAP Lambert Academic Publishing, 2013. - 269 p.